PFA fixation enables artifact-free super-resolution imaging of the actin cytoskeleton and associated proteins - Leyton-Puig, Daniela; Kedziora, Katarzyna M.; Isogai, Tadamoto; van den Broek, Bram; Jalink, Kees; Innocenti, Metello (Biology open, 2016)
Super-resolution microscopy (SRM) allows precise localization of proteins in cellular organelles and structures, including the actin cytoskeleton. Yet sample preparation protocols for SRM are rather anecdotal and still being optimized. Thus, SRM-based imaging of the actin cytoskeleton and associated proteins often remains challenging and poorly reproducible. Here, we show that proper paraformaldehyde (PFA)-based sample preparation preserves the architecture of the actin cytoskeleton almost as faithfully as gold-standard glutaraldehyde fixation. We show that this fixation is essential for proper immuno-based localization of actin-binding and actin-regulatory proteins involved in the formation of lamellipodia and ruffles, such as mDia1, WAVE2 and clathrin heavy chain, and provide detailed guidelines for the execution of our method. In summary, proper PFA-based sample preparation increases the multi-color possibilities and the reproducibility of SRM of the actin cytoskeleton and its associated proteins.